Efficacy of new generation insecticides for the management of shoot borer (Conogethes punctiferalis Guen.) (Lepidoptera: Crambidae) of turmeric (Curcuma longa L.) - S Devasahayam, C M Senthil Kumar, T K Jacob, (Journal of Spices and Aromatic Crops, 2019)
The efficacy of nine insecticides and a natural product was evaluated in the field at Peruvannamuzhi (Kerala) for the management of shoot borer (Conogethes punctiferalis), a major insect pest on turmeric (Curcuma longa). Pooled analysis of data for two years showed that chlorantraniliprole 0.01% treatment had the lowest mean pseudostem damage (0.3%) that was on par with lambda-cyhalothrin 0.01% (1.0%) and flubendiamide 0.02% (1.8%), when these insecticides were sprayed at fortnightly intervals from the second fortnight of July to the first fortnight of November. Fresh rhizome yield was highest in plots treated with lambda-cyhalothrin 0.01% (9.7 kg bed-1) that was on par with flubendiamide 0.02% (9.5 kg bed-1), chlorantraniliprole 0.01% (9.0 kg bed-1) and spinosad (9.0 kg bed-1). The trials indicated that reduced-risk/low-toxic insecticides such as chlorantraniliprole and flubendiamide can be utilized for the management of the pest with less hazard to the environment.